Zirconia ceramic and method of making and electronic product housing
Patent Information
- Application Number
- CN202211114892.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-14
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-09-14
AI Technical Summary
[0004]本发明的目的是为了克服现有的氧化锆陶瓷产品难以兼顾和均衡低密度、低介电常数、高抗冲击性以及易加工性的问题,提供了氧化锆陶瓷及制备方法与电子产品壳体
[0012] Through the above technical solution, this invention introduces appropriate proportions of magnesium oxide, aluminum oxide, and silicon oxide into the zirconia ceramic raw material, resulting in a zirconia ceramic with a specific elemental composition. Furthermore, the zirconia phase is doped with specific amounts of MgAl₂O₄ and ZrSiO₄ phases. These specific elements and phases work synergistically, giving the zirconia ceramic low density, low dielectric constant, high impact resistance, and good processability, thus effectively meeting the performance requirements of ceramic materials for electronic product casings. This zirconia ceramic also has a relatively low sintering temperature, placing less stringent demands on the performance of sintering equipment, which is beneficial for large-scale production and cost reduction.
Smart Images

Figure BDA0003845021740000181 
Figure BDA0003845021740000191
Abstract
Description
Technical Field
[0001] This invention relates to the field of zirconia ceramics technology, specifically to zirconia ceramics and their preparation methods, and to electronic product casings. Background Technology
[0002] Zirconia ceramics possess superior corrosion resistance, high hardness, and high strength compared to conventional ceramic materials, leading to their wide application in various fields. Although the toughness of zirconia ceramics (typically reaching 5-6 MPa·m) is... 1 / 2 While zirconia ceramics offer certain advantages over other conventional ceramics, they still suffer from weak impact resistance when used to fabricate large-area exterior components. When using zirconia ceramics to manufacture electronic product casings such as mobile phone back covers, the thinness of the casing amplifies the semi-transparency of the zirconia ceramic itself. Therefore, an ink coating is needed on the back of the casing to prevent the internal components from being seen, thus increasing production costs. Furthermore, with the widespread adoption of 5G mobile communication technology, users have increasingly higher requirements for the dielectric constant and density of ceramic casings for electronic products, making the reduction of dielectric constant and density an urgent issue.
[0003] To address the aforementioned issues, the industry currently often uses the addition of alumina to reduce the density and dielectric constant of zirconia ceramics. However, the high hardness and brittleness of alumina significantly increase the processing difficulty of zirconia ceramics, leading to low yield rates and making large-scale production impossible. Therefore, providing a zirconia ceramic with low density, low dielectric constant, high impact resistance, and good processability is of great significance for meeting the increasingly stringent comprehensive performance requirements of ceramic casings in 5G era electronic products. Summary of the Invention
[0004] The purpose of this invention is to overcome the problem that existing zirconia ceramic products are difficult to balance and achieve low density, low dielectric constant, high impact resistance and easy processing, and to provide zirconia ceramics, preparation methods and electronic product housings.
[0005] To achieve the above objectives, the first aspect of the present invention provides a zirconia ceramic, wherein the ceramic comprises, in terms of elements, Zr, Y, Mg, Al and Si; the phases of the ceramic comprise, in terms of, tetragonal zirconia, MgAl2O4 and ZrSiO4; wherein the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia.
[0006] A second aspect of this invention provides a method for preparing zirconia ceramics, comprising:
[0007] (1) Powder containing yttrium-stabilized zirconium oxide, magnesium oxide, aluminum oxide and silicon dioxide is wet-milled with water, dispersant and binder to obtain slurry, and the slurry is dried to obtain shaped powder;
[0008] (2) The shaped powder is sequentially shaped and sintered to obtain zirconium oxide ceramic;
[0009] The molar ratio of magnesium oxide to aluminum oxide in the powder is 1.
[0010] A third aspect of the present invention provides a zirconia ceramic prepared by the preparation method described in the second aspect above.
[0011] A fourth aspect of the present invention provides an electronic product housing containing the zirconia ceramic described in the first or third aspect above.
[0012] Through the above technical solution, this invention introduces appropriate proportions of magnesium oxide, aluminum oxide, and silicon oxide into the zirconia ceramic raw material, resulting in a zirconia ceramic with a specific elemental composition. Furthermore, the zirconia phase is doped with specific amounts of MgAl₂O₄ and ZrSiO₄ phases. These specific elements and phases work synergistically, giving the zirconia ceramic low density, low dielectric constant, high impact resistance, and good processability, thus effectively meeting the performance requirements of ceramic materials for electronic product casings. This zirconia ceramic also has a relatively low sintering temperature, placing less stringent demands on the performance of sintering equipment, which is beneficial for large-scale production and cost reduction. Detailed Implementation
[0013] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0014] The first aspect of the present invention provides a zirconia ceramic, wherein the ceramic comprises, in terms of elements, Zr, Y, Mg, Al and Si; the phases of the ceramic comprise, in terms of, tetragonal zirconia, MgAl2O4 and ZrSiO4; wherein the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia.
[0015] According to the present invention, the zirconia ceramic has a specific elemental composition. Based on the total weight of the ceramic, the ceramic contains, in terms of elements: 18.59-57.61 wt% Zr, 0.55-4.36 wt% Y, 3.67-11.83 wt% Mg, 7.6-26.6 wt% Al and 0.047-1.4 wt% Si.
[0016] According to the present invention, the zirconia ceramic, in addition to satisfying the above-mentioned elemental composition, preferably contains, based on the total weight of the ceramic, the following elements: 26.16-53.93 wt% Zr, 0.77-4.08 wt% Y, 4.22-10.14 wt% Mg, 9.5-22.8 wt% Al and 0.094-0.93 wt% Si.
[0017] According to the present invention, the molar ratio of Mg to Al in the zirconia ceramic is 1:2. By controlling the molar ratio of Mg to Al to be 1:2, a spinel-structured MgAl2O4 phase can be formed in the zirconia ceramic after sintering.
[0018] According to the present invention, the zirconia ceramic contains, in addition to the amounts of zirconium, yttrium, magnesium, aluminum and silicon as described above, essential oxygen and negligible amounts of impurity elements that do not affect the main properties of the zirconia ceramic.
[0019] In this invention, the elemental composition of the ceramic can be determined by X-ray fluorescence spectroscopy (XRF).
[0020] According to the present invention, the zirconia ceramic has a specific phase composition. Based on the total weight of the ceramic, the phase composition of the ceramic comprises: 20.8-79.7 wt% tetragonal zirconia, 20-70 wt% MgAl₂O₄, and 0.3-9.2 wt% ZrSiO₄;
[0021] Preferably, based on the total weight of the ceramic, the phase composition of the ceramic comprises: 33.8-74.4 wt% tetragonal zirconium oxide, 25-60 wt% MgAl2O4 and 0.6-6.2 wt% ZrSiO4.
[0022] In this invention, the tetragonal zirconium oxide refers to a room-temperature stable tetragonal zirconium oxide solid solution formed together with zirconium oxide using yttrium oxide as a stabilizer.
[0023] In this invention, room temperature refers to 20-30°C.
[0024] According to the present invention, by forming a mixture of tetragonal zirconium oxide, ZrSiO4 phase and spinel-structured MgAl2O4 phase with the above-mentioned specific quantitative relationship in zirconium oxide ceramic, the zirconium oxide ceramic can have low density and low dielectric constant, while its mechanical properties are significantly optimized, specifically manifested as further improvement in impact resistance, and excellent processability and low light transmittance.
[0025] According to the present invention, in the mixture of tetragonal zirconium oxide, ZrSiO4 phase and spinel-structured MgAl2O4 phase, the formation of the ZrSiO4 doped phase can significantly reduce the sintering temperature during the preparation of the zirconium oxide ceramic, while improving the impact resistance of the ceramic.
[0026] According to the present invention, in addition to the above-mentioned phases, the zirconia ceramic may also contain no more than 0.5 wt% (based on the total weight of the ceramic) of monoclinic zirconia.
[0027] In this invention, the phases and contents of the ceramic can be determined by X-ray diffraction (XRD).
[0028] According to the present invention, the zirconia ceramic has a low dielectric constant. Preferably, the dielectric constant of the zirconia ceramic is less than 25, and more preferably less than 23.
[0029] In this invention, the dielectric constant of the ceramic is determined using a dielectric constant network analyzer at 2 GHz.
[0030] According to the present invention, the zirconia ceramic has a low density, thereby achieving lightweighting. Preferably, the density of the zirconia ceramic is not greater than 5.4 g / cm³. 3 Further optimization is to select a concentration of no more than 5.3 g / cm³. 3 .
[0031] In this invention, the density of the ceramic is determined using Archimedes' method of water displacement.
[0032] According to the present invention, the zirconia ceramic has a suitable hardness that meets the requirements for use. Preferably, the hardness of the zirconia ceramic is not greater than 1550 Hv.
[0033] In this invention, the hardness of the ceramic is determined using a Vickers hardness tester and by indentation method (diamond indenter, test force 10 kg, test time 15 s).
[0034] According to the present invention, the zirconia ceramic exhibits good toughness. Preferably, the fracture toughness of the zirconia ceramic is not less than 4 MPa·m. 1 / 2 .
[0035] In this invention, the fracture toughness of ceramics is determined using a Vickers hardness tester and the indentation method (diamond indenter, test force 10 kg, test time 15 s).
[0036] According to the present invention, the zirconia ceramic exhibits excellent impact resistance. Preferably, the drop height of the zirconia ceramic is greater than 22 cm, and more preferably greater than 26 cm.
[0037] In this invention, a drop hammer impact test is used, and the impact resistance of ceramic materials is evaluated by the height of the drop hammer. During the test, the sample is placed on the test platform of the drop hammer impact tester, and a 60g drop hammer is used to strike the center of the sample from a height of 5cm. If no crack appears in the sample, the height of the drop hammer is increased by 5cm and the test continues. This process is repeated until a crack visible to the naked eye appears in the test sample. The drop hammer height value of the last strike is recorded as the drop hammer impact test result for that sample.
[0038] According to the present invention, the zirconia ceramic has good processing performance. Preferably, the thinning rate of the zirconia ceramic is greater than 27 filaments / h, more preferably greater than 29 filaments / h.
[0039] In this invention, the ceramic thinning rate is measured using the dimensional speed of a copper grinding disc, with a fixed time of 1 hour, and the thickness difference before and after copper grinding is determined. A faster thinning rate indicates better material machinability.
[0040] The zirconia ceramic provided by this invention possesses specific elements and phase composition that work synergistically to simultaneously exhibit the aforementioned overall performance indicators, including low density, low dielectric constant, high impact resistance, good mechanical and processing properties, and low light transmittance. Furthermore, it also has a relatively low sintering temperature (below 1480°C). When the elements, phase composition, and quantitative relationships contained in the ceramic do not meet the above-mentioned limiting conditions of this invention, it is impossible to obtain a zirconia ceramic product that simultaneously possesses the above-mentioned performance indicators.
[0041] A second aspect of the present invention provides a method for preparing reinforced zirconia ceramics, comprising:
[0042] (1) Powder containing yttrium-stabilized zirconium oxide, magnesium oxide, aluminum oxide and silicon dioxide is wet-milled with water, dispersant and binder to obtain slurry, and the slurry is dried to obtain shaped powder;
[0043] (2) The shaped powder is sequentially shaped and sintered to obtain zirconium oxide ceramic;
[0044] The molar ratio of magnesium oxide to aluminum oxide in the powder is 1.
[0045] According to the present invention, in step (1), the dispersant enables the powder to be more fully dispersed in water to form a uniform ceramic raw material slurry. Preferably, the weight ratio of the dispersant to the powder is (0.1-0.5):100.
[0046] In this invention, the scope of the dispersant is broad, and it can be a dispersant commonly used in the ceramics industry for preparing ceramic raw material slurries, preferably selected from hydroxypropyl methylcellulose and / or ammonium polyacrylate. It can be obtained in-house using conventional methods or a commercially available product; this invention does not have any particular limitation in this regard.
[0047] According to the present invention, in step (1), in order to facilitate the subsequent molding of the molding powder, preferably, the weight ratio of the binder to the powder is (2-5):100.
[0048] In this invention, the scope of the binder is relatively broad, and conventional molding binders in the ceramic field can be used, preferably polyvinyl alcohol and / or polyethylene glycol, and more preferably a combination of polyvinyl alcohol and polyethylene glycol.
[0049] In this invention, polyvinyl alcohol and polyethylene glycol can be obtained by conventional methods or by using commercially available products; this invention does not have any particular limitations on this.
[0050] According to the present invention, in step (1), based on the total weight of the powder, the powder contains: 27-79.9 wt% yttrium-stabilized zirconium oxide, 5.63-19.72 wt% magnesium oxide, 14.36-50.28 wt% aluminum oxide and 0.1-3 wt% silicon dioxide;
[0051] Preferably, based on the total weight of the powder, the powder contains: 38-74.8 wt% yttrium-stabilized zirconium oxide, 7-16.9 wt% magnesium oxide, 18-43.1 wt% aluminum oxide and 0.2-2 wt% silicon dioxide.
[0052] According to the present invention, in step (1), the amount of each raw material powder fed satisfies the elemental composition of the final zirconia ceramic. By controlling the molar ratio of magnesium oxide to aluminum oxide in the powder to be 1:1, and combined with the sintering conditions, a spinel-structured MgAl2O4 doped phase and a ZrSiO4 doped phase can be formed in the zirconia matrix. That is, the zirconia ceramic obtained contains a specific ratio of tetragonal zirconia, ZrSiO4 phase and spinel-structured MgAl2O4 phase, which makes the zirconia ceramic have low density, low dielectric constant, high impact resistance, and excellent processability. The introduction of silicon dioxide in the raw material powder can significantly reduce the sintering temperature of the zirconia ceramic (below 1480°C), which not only reduces energy consumption but also improves the impact resistance of the zirconia ceramic.
[0053] According to the present invention, in step (1), in the powder containing yttrium-stabilized zirconium oxide, magnesium oxide, aluminum oxide and silicon dioxide, preferably, the median particle size of yttrium-stabilized zirconium oxide is 0.3-0.6 μm, the median particle size of magnesium oxide is 0.1-0.2 μm, the median particle size of aluminum oxide is 0.15-0.6 μm, and the median particle size of silicon dioxide is 0.2-0.5 μm.
[0054] According to the present invention, preferably, based on the total amount of yttrium-stabilized zirconium oxide, the yttrium-stabilized zirconium oxide contains 1.5-4 mol% yttrium oxide.
[0055] According to the present invention, in step (1), the wet milling preferably includes ball milling and sand milling performed sequentially. First, the powder containing yttrium-stabilized zirconium oxide, magnesium oxide, aluminum oxide and silicon dioxide that meets the above-mentioned limiting conditions is placed in a ball mill, water is added for ball milling, then transferred to a sand mill, water is added and the above-mentioned dispersant is added for sand milling, and finally the above-mentioned binder is added and stirred to obtain a uniform slurry.
[0056] According to the present invention, in the wet milling process, preferably, the ball milling time is 2-4 hours and the sand milling time is 3-6 hours. The slurry obtained from the wet milling has a solid content of 20-60 wt% and a median particle size of 0.5-0.7 μm for the solid phase components.
[0057] According to the present invention, preferably, the equipment used for wet milling is equipped with a wear-resistant zirconia liner and uses zirconia grinding media to minimize the amount of impurities introduced into the ceramic raw material slurry during the wet milling process. Furthermore, the present invention does not impose particular limitations on the proportions of raw material powder, water, and grinding media used in the wet milling process, nor on the operating parameters of the wet milling equipment, as long as the slurry obtained from the wet milling meets the aforementioned defined median particle size range for the solid components.
[0058] According to the present invention, in step (1), there is no particular limitation on the drying method, as long as the slurry can be dehydrated and dried to obtain a molding powder that meets the molding process requirements. Preferably, spray drying can be used, with conditions including: inlet air temperature of 200-300℃, outlet air temperature of 90-130℃, and centrifugal speed of 10-20 revolutions per second.
[0059] According to the present invention, in step (2), there is no particular limitation on the molding process, and various molding processes in the art can be used, such as dry pressing, isostatic pressing, injection molding, etc. Those skilled in the art can select and adjust the molding process and molding parameters according to the requirements of the target preform.
[0060] According to the present invention, in step (3), the sintering can be carried out in conventional equipment for ceramic sintering. Preferably, the sintering conditions include: a temperature of 1400-1480℃, more preferably 1430-1470℃; and a time of 1-4h, more preferably 2-3h.
[0061] According to the present invention, the preparation method further includes: grinding and polishing the sintered product, and then laser cutting it into the desired shape to obtain the final zirconia ceramic product.
[0062] A third aspect of the present invention provides a zirconia ceramic prepared by the preparation method described in the second aspect above.
[0063] According to the present invention, the zirconia ceramic prepared by the preparation method comprises, in terms of elements: Zr, Y, Mg, Al and Si; the phases of the ceramic comprise: tetragonal zirconia, MgAl2O4 and ZrSiO4; the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia.
[0064] According to the present invention, the zirconia ceramic prepared by the method described herein has a specific elemental composition. Based on the total weight of the ceramic, the ceramic contains, elementally, 18.59-57.61 wt% Zr, 0.55-4.36 wt% Y, 3.67-11.83 wt% Mg, 7.6-26.6 wt% Al and 0.047-1.4 wt% Si.
[0065] Preferably, based on the total weight of the ceramic, the ceramic contains, in terms of elements: 26.16-53.93 wt% Zr, 0.77-4.08 wt% Y, 4.22-10.14 wt% Mg, 9.5-22.8 wt% Al and 0.094-0.93 wt% Si.
[0066] According to the present invention, in the zirconia ceramic prepared by the preparation method, the molar ratio of Mg to Al, calculated by element, is 1:2.
[0067] According to the present invention, the zirconia ceramic prepared by the preparation method contains, in addition to the above-mentioned amounts of zirconium, yttrium, magnesium, aluminum and silicon, the necessary oxygen element, as well as a negligible amount of impurity elements that do not affect the main properties of the zirconia ceramic.
[0068] According to the present invention, the zirconia ceramic prepared by the method described herein has a specific phase composition. Based on the total weight of the ceramic, the phase composition of the ceramic comprises: 20.8-79.7 wt% tetragonal zirconia, 20-70 wt% MgAl₂O₄, and 0.3-9.2 wt% ZrSiO₄.
[0069] Preferably, based on the total weight of the ceramic, the phase composition of the ceramic comprises: 33.8-74.4 wt% tetragonal zirconium oxide, 25-60 wt% MgAl2O4 and 0.6-6.2 wt% ZrSiO4.
[0070] According to the present invention, the zirconia ceramic prepared by the aforementioned method has a dielectric constant of less than 25 and a density of no more than 5.4 g / cm³. 3 Hardness not greater than 1550 Hv, fracture toughness not less than 4 MPa·m 1 / 2 The thinning rate is greater than 27 filaments / h, and the drop hammer height obtained from the drop hammer impact test is greater than 22 cm. It exhibits comprehensive properties including low density, low dielectric constant, high impact resistance, good mechanical properties, and good processability. Furthermore, the sintering temperature required to prepare this zirconia ceramic is relatively low, below 1480℃. The testing methods for dielectric constant, density, hardness, fracture toughness, thinning rate, and drop hammer height are the same as those described in the first aspect of this invention and will not be repeated here.
[0071] A fourth aspect of the present invention provides an electronic product housing containing the zirconia ceramic described in the first or third aspect above.
[0072] The present invention will be described in detail below through embodiments. In the following embodiments and comparative examples,
[0073] Unless otherwise specified, all materials used are common commercially available products.
[0074] Example 1
[0075] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm), aluminum oxide powder (median particle size 0.2 μm), and silica powder (median particle size 0.3 μm) are mixed to obtain 200 g of composite powder (containing 69.5 wt% of the above-mentioned zirconia powder, 8.45 wt% of MgO, 21.55 wt% of Al2O3, and 0.5 wt% of SiO2).
[0076] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0077] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1450℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as P1).
[0078] XRF testing results show that the elemental composition of P1 includes: 48.8 wt% Zr, 2.9 wt% Y, 5.1 wt% Mg, 11.5 wt% Al and 0.3 wt% Si.
[0079] XRD analysis showed that the phase composition of P1 included: 67.9 wt% tetragonal zirconium oxide, 30.2 wt% MgAl2O4, 1.6 wt% ZrSiO4 and 0.3 wt% monoclinic zirconium oxide.
[0080] Example 2
[0081] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm), aluminum oxide powder (median particle size 0.2 μm), and silica powder (median particle size 0.3 μm) are mixed to obtain 200 g of composite powder (containing 74 wt% of the above-mentioned zirconia powder, 7.18 wt% of MgO, 18.32 wt% of Al2O3, and 0.5 wt% of SiO2).
[0082] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0083] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1440℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as P2).
[0084] XRF testing results show that the elemental composition of P2 includes: 52.1 wt% Zr, 3.1 wt% Y, 4.4 wt% Mg, 9.7 wt% Al and 0.3 wt% Si.
[0085] XRD analysis results show that the phase composition of P2 includes: 72.7 wt% tetragonal zirconium oxide, 25.6 wt% MgAl2O4, 1.5 wt% ZrSiO4 and 0.2 wt% monoclinic zirconium oxide.
[0086] Example 3
[0087] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm), aluminum oxide powder (median particle size 0.2 μm), and silica powder (median particle size 0.3 μm) are mixed to obtain 200 g of composite powder (containing 59.5 wt% of the above-mentioned zirconia powder, 11.27 wt% of MgO, 28.73 wt% of Al2O3, and 0.5 wt% of SiO2).
[0088] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0089] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1465℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as P3).
[0090] XRF testing results show that the elemental composition of P3 includes: 41.8 wt% Zr, 2.5 wt% Y, 6.8 wt% Mg, 15.33 wt% Al and 0.2 wt% Si.
[0091] XRD analysis results show that the phase composition of P3 includes: 57.7 wt% tetragonal zirconium oxide, 40.3 wt% MgAl2O4, 1.6 wt% ZrSiO4 and 0.4 wt% monoclinic zirconium oxide.
[0092] Example 4
[0093] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm), aluminum oxide powder (median particle size 0.2 μm), and silica powder (median particle size 0.3 μm) are mixed to obtain 200 g of composite powder (containing 77.5 wt% of the above-mentioned zirconia powder, 6.19 wt% of MgO, 15.81 wt% of Al2O3, and 0.5 wt% of SiO2).
[0094] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0095] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1435℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as P4).
[0096] XRF testing results show that the elemental composition of P4 includes: 54.5 wt% Zr, 3.3 wt% Y, 8.9 wt% Mg, 20.1 wt% Al and 0.3 wt% Si.
[0097] XRD analysis results show that the phase composition of P4 includes: 75.8 wt% tetragonal zirconium oxide, 22.2 wt% MgAl2O4, 1.7 wt% ZrSiO4 and 0.3 wt% monoclinic zirconium oxide.
[0098] Example 5
[0099] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm), aluminum oxide powder (median particle size 0.2 μm), and silica powder (median particle size 0.3 μm) are mixed to obtain 200 g of composite powder (containing 30 wt% of the above-mentioned zirconia powder, 19.67 wt% MgO, 50.18 wt% Al2O3, and 0.15 wt% SiO2).
[0100] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0101] (2) The above-mentioned molding powder is shaped into blanks (by dry pressing). After the blanks are dried, they are placed in a kiln and sintered at 1470℃ for 2 hours to obtain sintered products. Then, they are successively ground and polished, and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain zirconia ceramic products (denoted as P5).
[0102] XRF testing results show that the elemental composition of P5 includes: 21.1 wt% Zr, 1.3 wt% Y, 11.7 wt% Mg, 26.5 wt% Al and 0.09 wt% Si.
[0103] XRD analysis results show that the phase composition of P5 includes: 29.4 wt% tetragonal zirconium oxide, 69.9 wt% MgAl2O4, 0.5 wt% ZrSiO4 and 0.2 wt% monoclinic zirconium oxide.
[0104] Example 6
[0105] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm), aluminum oxide powder (median particle size 0.2 μm), and silica powder (median particle size 0.3 μm) are mixed to obtain 200 g of composite powder (containing 69.7 wt% of the above-mentioned zirconia powder, 8.45 wt% of MgO, 21.55 wt% of Al2O3, and 0.3 wt% of SiO2).
[0106] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0107] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1475℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as P6).
[0108] XRF testing results show that the elemental composition of P6 includes: 48.9 wt% Zr, 2.9 wt% Y, 5.2 wt% Mg, 11.6 wt% Al and 0.2 wt% Si.
[0109] XRD analysis results show that the phase composition of P6 includes: 68.7 wt% tetragonal zirconium oxide, 30.2 wt% MgAl2O4, 0.9 wt% ZrSiO4 and 0.2 wt% monoclinic zirconium oxide.
[0110] Comparative Example 1
[0111] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium oxide stabilized and alumina powder (median particle size 0.2 μm) are mixed to obtain 200 g of composite powder (containing 70 wt% of the above-mentioned zirconia powder and 30 wt% Al2O3).
[0112] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0113] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1550℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as D1).
[0114] XRF test results show that the elemental composition of D1 includes: 49.5 wt% Zr, 3.4 wt% Y, and 16.1 wt% Al.
[0115] XRD analysis results show that the phase composition of D1 includes: 69.6 wt% tetragonal zirconium oxide, 30.2 wt% Al2O3 and 0.2 wt% monoclinic zirconium oxide.
[0116] Comparative Example 2
[0117] Raw material preparation: 200g of zirconia powder (median particle size 0.5μm) containing 3mol% yttrium-stabilized zirconia is used (of which 100wt% of the above zirconia powder is used).
[0118] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0119] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1450℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as D2).
[0120] XRF test results show that the elemental composition of D2 includes: 70.3 wt% Zr and 4.3 wt% Y.
[0121] XRD test results show that the phase composition of D2 includes: 99.6 wt% tetragonal zirconium oxide and 0.4 wt% monoclinic zirconium oxide.
[0122] Comparative Example 3
[0123] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm) and aluminum oxide powder (median particle size 0.2 μm) are mixed to obtain 200 g of composite powder (containing 70 wt% of the above-mentioned zirconia powder, 8.45 wt% of MgO and 21.55 wt% of Al2O3).
[0124] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0125] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1550℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as D3).
[0126] XRF test results show that the elemental composition of D3 includes: 49.2 wt% Zr, 2.9 wt% Y, 5.2 wt% Mg, and 11.6 wt% Al.
[0127] XRD analysis results show that the phase composition of D3 includes: 69.6 wt% tetragonal zirconium oxide, 30.2 wt% MgAl2O4 and 0.2 wt% monoclinic zirconium oxide.
[0128] Comparative Example 4
[0129] Raw material preparation: Zirconia powder (median particle size 0.5 μm) containing 3 mol% yttrium-stabilized zirconia powder, magnesium oxide powder (median particle size 0.15 μm) and aluminum oxide powder (median particle size 0.2 μm) are mixed to obtain 200 g of composite powder (containing 70 wt% of the above-mentioned zirconia powder, 8.45 wt% of MgO and 21.55 wt% of Al2O3).
[0130] (1) Place the above 200g composite powder in a ball mill, add water and ball mill for 4h; then transfer the ball milled product to a sand mill, add water and add ammonium polyacrylate (the weight ratio of ammonium polyacrylate to the above composite powder is 0.3:100) and sand mill for 4h; finally add binder (a mixture of PEG4000 and PVA in a molar ratio of 1:1, the weight ratio of binder to the above composite powder is 4:100) and stir for 2h to obtain a slurry (solid content is 50wt%, and the median particle size of the solid phase component is 0.55μm); spray dry the above slurry (the operating parameters of the spray drying tower include: inlet air temperature of 220℃, outlet air temperature of 120℃, and centrifugal speed of 15 rpm) to obtain shaped powder;
[0131] (2) The above-mentioned molding powder is shaped into a blank (by dry pressing). After the blank is dried, it is placed in a kiln and sintered at 1450℃ for 2 hours to obtain a sintered product. Then, it is polished by flat grinding and laser-cut into the shape of a mobile phone back cover (size 150mm×75mm×0.6mm) to obtain a zirconia ceramic product (denoted as D4).
[0132] XRF test results show that the elemental composition of D4 includes: 49.2 wt% Zr, 2.9 wt% Y, 5.2 wt% Mg, and 11.6 wt% Al.
[0133] XRD analysis showed that the phase composition of D4 included 60.6 wt% tetragonal zirconium oxide, 30.1 wt% MgAl2O4, and 9.3 wt% monoclinic zirconium oxide.
[0134] Test case
[0135] The zirconia ceramics P1-P6 and D1-D4 prepared in Examples 1-6 and Comparative Examples 1-4 were tested for hardness, fracture toughness, and density (the average number of pits per 10mm×10mm area on the large surface of the polished product, with the pit diameter greater than 20um). The results are shown in Table 1.
[0136] Table 1
[0137]
[0138] As can be seen from Table 1, the zirconia ceramics P1-P6 provided by this invention have a hardness of less than 1550 Hv, while their fracture toughness is not less than 4 MPa·m. 1 / 2 It exhibits high density. Among P1-P6, the hardness of the product gradually increases with the increase of MgAl2O4 content, while the fracture toughness shows a gradual decreasing trend. In addition, as the silica content in the raw materials for the preparation of P1-P6 increases, the sintering densification temperature gradually decreases.
[0139] Test Example 2
[0140] The dielectric constant, density, processability and drop hammer impact resistance of the zirconia ceramics P1-P6 and D1-D4 prepared in Examples 1-6 and Comparative Examples 1-4 were tested, and the sintering temperature was recorded. The results are shown in Table 2.
[0141] Table 2
[0142]
[0143] As can be seen from Table 2, the zirconia ceramics P1-P6 provided by this invention have a dielectric constant of less than 25 and a density of no more than 5.4 g / cm³. 3 The product exhibits low dielectric constant and low density; a thinning rate greater than 27 filaments / h, resulting in good processing performance; a drop hammer height greater than 22 cm, providing excellent impact resistance; and a relatively low sintering temperature, below 1480℃. Specifically, comparing P1 and D3, it is evident that the addition of silica in the raw materials significantly reduces the densification temperature and improves the impact resistance of the product to a certain extent. D3's high sintering temperature places stringent demands on the performance of the sintering equipment, making it difficult to purchase sintering equipment suitable for mass production, thus hindering large-scale manufacturing. Comparing P1 and D4, without the use of silica, at the same sintering temperature of 1450℃, the density and mechanical properties of the resulting zirconia ceramic product D4 are significantly inferior to those of P1. This indicates that in addition to lowering the sintering temperature, the coexistence and interaction of the ZrSiO4 phase formed by silica with tetragonal zirconia and MgAl2O4 are also key to obtaining the comprehensive performance of the zirconia ceramic of this invention.
[0144] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A zirconia ceramic, characterized in that, The ceramic contains, in terms of elements, Zr, Y, Mg, Al, and Si; the ceramic phase consists of tetragonal zirconium oxide and spinel-structured MgAl2O. 4、 It is composed of ZrSiO4 and monoclinic zirconium oxide; the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide; Based on the total weight of the ceramic, the ceramic contains, in terms of elements: 18.59-57.61 wt% Zr, 0.55-4.36 wt% Y, 3.67-11.83 wt% Mg, 7.6-26.6 wt% Al and 0.047-1.4 wt% Si; Based on the total weight of the ceramic, the phase composition of the ceramic consists of 33.8-74.4 wt% tetragonal zirconium oxide, 25-60 wt% spinel-structured MgAl2O4, 0.6-6.2 wt% ZrSiO4, and no more than 0.5 wt% monoclinic zirconium oxide. The ceramic is prepared according to the following method: (1) Powder containing yttrium-stabilized zirconium oxide, magnesium oxide, aluminum oxide and silicon dioxide is wet-milled with water, dispersant and binder to obtain slurry, and the slurry is dried to obtain shaped powder; (2) The shaped powder is sequentially shaped and sintered to obtain zirconia ceramic; Wherein, the molar ratio of magnesium oxide to aluminum oxide in the powder is 1; In step (1), based on the total weight of the powder, the powder contains: 27-79.9 wt% yttrium-stabilized zirconium oxide, 5.63-19.72 wt% magnesium oxide, 14.36-50.28 wt% aluminum oxide and 0.1-3 wt% silicon dioxide; In step (2), the sintering conditions include: a temperature of 1400-1480℃ and a time of 1-4h.
2. The ceramic according to claim 1, wherein, Based on the total weight of the ceramic, the ceramic contains, in terms of elements: 26.16-53.93 wt% Zr, 0.77-4.08 wt% Y, 4.22-10.14 wt% Mg, 9.5-22.8 wt% Al and 0.094-0.93 wt% Si.
3. The ceramic according to claim 1 or 2, wherein, The dielectric constant of the ceramic is less than 25.
4. The ceramic according to claim 1 or 2, wherein, The density of the ceramic is not greater than 5.4 g / cm³. 3 .
5. The ceramic according to claim 1 or 2, wherein, The hardness of the ceramic is not greater than 1550 Hv.
6. The ceramic according to claim 1 or 2, wherein, The fracture toughness of the ceramic is not less than 4 MPa·m 1 / 2 .
7. The ceramic according to claim 1 or 2, wherein, The ceramic has a thinning rate greater than 27 filaments / h.
8. The ceramic according to claim 1 or 2, wherein, The drop height of the ceramic is greater than 22cm.
9. The ceramic according to claim 1 or 2, wherein, The sintering temperature of the ceramic is below 1480℃.
10. The ceramic according to claim 1, wherein, In step (1), the weight ratio of the dispersant to the powder is (0.1-0.5):
100.
11. The ceramic according to claim 1, wherein, In step (1), the weight ratio of the binder to the powder is (2-5):
100.
12. The ceramic according to claim 1 or 10, wherein, In step (1), the dispersant is selected from hydroxypropyl methylcellulose and / or ammonium polyacrylate.
13. The ceramic according to claim 1 or 11, wherein, In step (1), the adhesive is selected from polyvinyl alcohol and / or polyethylene glycol.
14. The ceramic according to any one of claims 1, 10, and 11, wherein, Based on the total weight of the powder, the powder contains: 38-74.8 wt% yttrium-stabilized zirconium oxide, 7-16.9 wt% magnesium oxide, 18-43.1 wt% aluminum oxide and 0.2-2 wt% silicon dioxide.
15. The ceramic according to claim 1, wherein, In step (1), the median particle size of yttrium-stabilized zirconium oxide is 0.3-0.6 μm, the median particle size of magnesium oxide is 0.1-0.2 μm, the median particle size of aluminum oxide is 0.15-0.6 μm, and the median particle size of silicon dioxide is 0.2-0.5 μm.
16. The ceramic according to claim 1 or 15, wherein, The yttrium-stabilized zirconium oxide contains 1.5-4 mol% yttrium oxide.
17. The ceramic according to claim 1, wherein, The median particle size of the solid phase component in the slurry is 0.5-0.7 μm.
18. The ceramic according to claim 1, wherein, In step (2), the sintering conditions include: a temperature of 1430-1470℃ and a time of 2-3h.
19. A casing for an electronic product, characterized in that, The electronic product housing contains zirconia ceramic as described in any one of claims 1-18.
Citation Information
Patent Citations
Zirconium oxide ceramic used for oil and gas well and preparation method thereof
CN105236962A
Method for preparing ZrO2 / ZrSiO4 multiphase ceramic through hot pressed sintering and application of ZrO2 / ZrSiO4 multiphase ceramic to radionuclide solidification
CN112142463A
Zirconia ceramic as well as preparation method and application thereof
CN112537957A